Synthesis and Chiral Separation of Fibratol, Isopropyl 2-(4-((4-chlorophenyl)(hydroxyl) methyl)-phenoxy)-2-methylpropanoate - Kotheimer, Amanda E. (Int J Org Chem (Irvine), 2018)
Practical synthetic route for the formation of enantiomeric mixture of Isopropyl 2-(4-((4-chlorophenyl)(hydroxyl)methyl)phenoxy)-2-methylpropanoate (Fibratol 2a/b) from isopropyl 2-(4-(4-chlorobenzoyl)phenoxy)-2-methylpropanoate (Fenofibrate 1) has been developed. Method has also been established for the chiral separation of enantiomers of Fibratol 2a/b that is synthesized using the route mentioned above. The optical activity determined for enantiomerically separated Fibratol (2a) and Fibratol (2b) are −5.2° and 8.0° which reflect their ability to rotate plane polarized light counterclockwise (levo) and clockwise (dextro), respectively.